Determination of the efficiency of single-photon emission computed tomography with 99mTc-HMPAO-labelled leukocytes in the diagnosis of myocarditis: Comparison of scintigraphic and histological data - S. I. Sazonova; Yu. N. Il’yushenkova; R. E. Batalov; Yu. V. Rogovskaya; Yu. B. Lishmanov; S. V. Popov (Вестник рентгенологии и радиологии, 2016)
Objective: to determine the efficiency of single-photon emission computed tomography (SPECT) with 99mTc-HMPAOlabelled leukocytes in diagnosing myocarditis, by comparing scintigraphic and histological data.Material and methods. The investigation enrolled 35 patients with suspected myocarditis, who were planned to undergo coronaroventriculography or intervention with endomyocardial biopsy. Prior to endomyocardial biopsy, all the patients underwent myocardial scintigraphy using 99mTC-exametazime-labelled leukocytes. The results of myocardial scintigraphic and histological examinations were compared.Results. Abnormal myocardial 99mTc-HMPAO-labelled leukocyte accumulation was detected in 7 (20%) examinees. Myocarditis was histologically verified in 9 (25.7%) persons. Our findings showed that the sensitivity of 99mTc-HMPAO-labelled leukocyte SPECT in diagnosing myocardial inflammatory changes was 62%; its specificity and diagnostic accuracy were 92% and 85%, respectively.Conclusion. 99mTc-HMPAO-labelled leukocyte scintigraphy is today one of a few procedures for the primary noninvasive diagnosis of myocardial inflammation. However, in view of its  sufficiently low sensitivity and laboriousness and the high cost of consumables, the technique is irrationally used in routine clinical practice.